Online challenge related self-harm in children and adolescents: two case reports - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2019)
The contagious nature of suicides which is called as Werther's effect characterized by increase of suicidal behaviors after suicide reports on media and fictional portrayal of it on television is a well-known phenomenon. A new fashion of viral games which were claimed to have encouraged self-harm among children and adolescents are frightening families. We will discuss two adolescent cases who evaluated in outpatient service for online challenge related self-harm behavior. Psychiatric evaluation revealed that both children were suffering from psychiatric disorders, had peer problems and were socially isolated. This is the first paper from Turkey which reported that viral games might prod children and adolescents for self-harm.
Keywords: self-harm; children; online challenge; Blue Whale; Momo; suicide